2011
DOI: 10.1080/02701367.2011.10599806
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and Delayed Onset Muscle Soreness Do Not Vary During the Menstrual Cycle

Abstract: The purpose of this study was to determine if a difference in interleukin-6 (IL-6) and delayed onset muscles soreness (DOMS) exists in two different phases of the menstrual cycle. Nine runners performed one 75-min high-intensity interval running session during the early follicular (EF) phase and once during the midluteal (ML) phase of the menstrual cycle. Estrogen and progesterone levels were significantly reduced in the EF phase when compared to the ML phase. IL-6 levels increased from pre- to postexercise in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 56 publications
0
27
4
Order By: Relevance
“…In line with that, our lacking time-differences in IL-6 concentration between pre-trial and 2 h could be also due to the exercise modality. In the present exercise protocol, stimulus duration as well as the muscle mass involved in the exercise may be insufficient to increase IL-6 from pre-trial levels [15]. This has been demonstrated following aerobic protocols [40] which are generally long-lasting and involve larger muscle groups.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In line with that, our lacking time-differences in IL-6 concentration between pre-trial and 2 h could be also due to the exercise modality. In the present exercise protocol, stimulus duration as well as the muscle mass involved in the exercise may be insufficient to increase IL-6 from pre-trial levels [15]. This has been demonstrated following aerobic protocols [40] which are generally long-lasting and involve larger muscle groups.…”
Section: Discussionmentioning
confidence: 89%
“…Another factor possibly involved in IL-6 changes may be the modality of exercise. A previous study obtained higher values of IL-6 in the mid-follicular phase in comparison to the MLP after a continuous running protocol [10], while a different study obtained no differences between the EFP and the MLP following a running protocol [15]. As such, more research is needed to clarify whether different exercise modalities could facilitate different increases in IL-6 in relation to menstrual cycle phase.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Some studies did in fact confirm higher cytokine levels in females, especially in the context of estrogen stimulation [52]. However, other studies reported that IL-6 levels did not change during the menstrual cycle [53]. Although estrogens were shown to be able to slightly modulate cytokine levels, the variations observed were usually not significant or only approached significance when considering stimulations at various periods of the menstrual cycle.…”
Section: Reviewmentioning
confidence: 99%